(untitled) (Global Journals of Research in Engineering, 2013)
This paper presents a novel distribution power flow algorithm to estimate losses and analyze unbalanced distribution systems. An unbalanced distribution network is decomposed into clusters. The unbalanced laterals are solved using the backward/forward sweep method in each phase. The clustering of total network makes faster computation. The three phase modeling of all the distribution transformers, feeders, shunt capacitors and loads compile efficient algorithm. Load modeling is voltage dependent which makes up the load as voltage sensitive. The proposed method is tested on the IEEE 13 Node test system and the results are verified.